Co-constructing Knowledge to Benefit an Innovative Social Work Practicum: A Participatory Action Research (PAR) and Integrated Knowledge Translation (iKT) Approach - Sanders, Jane; Seale, Ariel; Bernal, Esther; Landon, Jessica; Sutton, Emma; Sullivan, Hayley; Reed, Andrew; Antia, Hazel; Arundel, M.K.; Csiernik, Rick (Canadian Social Work Review / Revue canadienne de service social, 2025)
This participatory action research (PAR) study is of an innovative virtual pilot practicum program developed through a university – school board partnership to provide relevant experiential learning for social work students pursuing their bachelor’s and master’s degrees while delivering social work services to the community. The Support and Aid to Families Electronically (SAFE) program employed technology novel to the School of Social Work, supported a service user population new to its students, engaged students in ground-up policy and protocol development, and instituted in-house practicum supervision for the first time. PAR was incorporated at the outset, along with an integrated knowledge translation (iKT) approach. The principal investigator supported the student-researcher participants to develop and conduct their own research on this learning opportunity, facilitating co-ownership and co-authorship of this work (Lind, 2007). Over 312 pages of data were collected through journaling and a group chat initiated by the social work students out of a need for connection during this novel virtual practicum. Using reflexive thematic analysis (Braun & Clarke, 2021), the students identified four main themes: program development, collaboration and problem-solving, peer support, and the importance of community creation. These themes told a story of a community of learning, as the seven students turned to each other for expertise within the group rather than viewing educators as the only experts able to provide knowledge (Brown & Campione, 2013). This mutual support among the student-researchers facilitated a sense of power and authority while actively engaged in the processes of learning (Groundwater-Smith & Mockler, 2016). This co-constructed research facilitated the co-construction of the practicum to the benefit of both students and service users.